Integrated metabolomic and transcriptomic analyses revealed the distribution of saponins in Panax notoginseng - Guangfei Wei; Linlin Dong; Juan Yang; Lianjuan Zhang; Jiang Xu; Feng Yang; Ruiyang Cheng; Ran Xu; Shilin Chen (Elsevier, 2018)
Panax notoginseng is famous for its important therapeutic effects. Saponins are bioactive compounds found in different parts and developmental stages of P. notoginseng plants. Thus, it is urgently to study saponins distribution in different parts and growth ages of P. notoginseng plants. In this study, potential biomarkers were found, and their chemical characteristic differences were revealed through metabolomic analysis. High-performance liquid chromatography data indicated the higher content of saponins (i.e., Rg1, Re, Rd, and Rb1) in the underground parts than that in the aerial parts. 20(S)-Protopanaxadiol saponins were mainly distributed in the aerial parts. Additionally, the total saponin content in the 3-year-old P. notoginseng plant (188.0 mg/g) was 1.4-fold higher than that in 2-year-old plant (130.5 mg/g). The transcriptomic analysis indicated the tissue-specific transcription expression of genes, namely, PnFPS, PnSS, PnSE1, PnSE2, and PnDS, which encoded critical synthases in saponin biosyntheses. These genes showed similar expression patterns among the parts of P. notoginseng plants. The expression levels of these genes in the flowers and leaves were 5.2fold higher than that in the roots and fibrils. These results suggested that saponins might be actively synthesized in the aerial parts and transformed to the underground parts. This study provides insights into the chemical and genetic characteristics of P. notoginseng to facilitate the synthesis of its secondary metabolites and a scientific basis for appropriate collection and rational use of this plant. KEY WORDS: Panax notoginseng, Saponin, Growth years, Metabolomic analyses, Gene expression